Effective Strategies for Cross-Cultural Business Negotiations - Liu, Xueqing (International Journal of Global Economics and Management, 2024)
With the acceleration of globalization, cross-cultural business negotiations have become increasingly important in international trade and business cooperation. This paper aims to explore effective strategies for conducting business negotiations in different cultural contexts, helping companies succeed in cross-cultural environments. Through a review of existing literature and analysis of multiple case studies, this paper identifies common challenges in cross-cultural business negotiations, such as language barriers, communication misunderstandings, differences in negotiation styles, and varying values and trust-building mechanisms. To address these challenges, the paper proposes various effective strategies, including building trust and relationships, employing effective communication techniques, respecting cultural differences, and maintaining flexibility and adaptability. Additionally, by comparing successful and unsuccessful cases, the paper summarizes the lessons learned from cross-cultural business negotiations, providing practical guidance for companies in future negotiations. Ultimately, the paper emphasizes the critical role of cultural sensitivity in cross-cultural business negotiations and calls for companies to enhance their cross-cultural communication skills in the context of globalization.